Chinese migrants and Africa's development : new imperialists or agents of change? - Mohan, Giles, 1966- (London : Zed Books, 2014)
China's recent stepping up of relations with Africa is one of the most significant developments on the African continent for decades. For some it promises an end to Africa's dependent aid relationships as the Chinese bring expertise, technology, and a stronger business focus. But for others it is no more than a new form of imperialism. This book is the first to systematically study the motivations, relationships, and impact of this migration. It focuses not just on the Chinese migrants but also on the perceptions of, and linkages to, their African 'hosts'. By studying this everyday interaction we get a much richer picture of whether this is South-South cooperation, as the political leaders would have us believe, or a more complex relationship that can both compromise and encourage African development.
Includes bibliographical references (p. 165-178) and index.
Keywords: Foreign workers, Chinese -- Africa; Africa -- Economic conditions; Africa -- Foreign economic relations -- China; China -- Foreign economic relations -- Africa